The Value of Circulating Tumor Cells in the Prognosis and Treatment of Pancreatic Cancer - Luo, Kai; Wang, Xiangkun; Zhang, Xudong; Liu, Zhongyuan; Huang, Shuai; Li, Renfeng (Frontiers in Oncology, 2022)
In the past few decades, tumor diagnosis and treatment theory has developed in varieties of directions. The number of people die from pancreatic cancer is rising when the mortality rate of other common tumors is dropping. Traditional imaging methods show the boundaries of pancreatic tumor, but they are not sufficient to judge early micrometastasis. Although carcinoembryonic antigen (CEA) and carbohydrate antigen19-9 (CA19-9) have the obvious advantages of simplicity and minimal invasiveness, these biomarkers obviously lack sensitivity and specificity. Circulating tumor cells (CTCs) has attracted attention as a non-invasive, dynamic and real-time liquid biopsy technique for analyzing tumor characteristics. With the continuous development of new CTCs enrichment technologies, substantial progress has been made in the basic research of CTCs clinical application prospects. In many metastatic cancers, CTCs has been studied as an independent prognostic factor. This article reviews the research progress of CTCs in the treatment and prognosis of pancreatic cancer.